Perencanaan Tujuan dan Sasaran Evaluasi Kinerja - Muhammad Rizky Efendi; Khoirotun Nuroh; Adi Lukman Hakim (Journal Of Business, Finance, and Economics (JBFE), 2025)
This research examines the strategic role of performance management in optimizing organizational human resources through measurable goal setting and systematic performance evaluation. Using a literature study method with a descriptive qualitative approach, this research analyzes the relationship between goal planning, performance evaluation, and organizational goal achievement. The research findings indicate that setting goals aligned with the organizational vision is a crucial foundation for shaping productive work behavior and enhancing employee commitment. The study’s findings also suggest that misalignment between individual and organizational goals can decrease employee motivation and productivity. Effective performance management, accompanied by mature goal planning and periodic evaluation, has been shown to strengthen the reciprocal relationship between the organization and its employees, thereby contributing to improved performance and the achievement of organizational competitive advantage. Additionally, the study highlights that consistent communication, transparent feedback, and continuous capacity building are essential to ensure that employees clearly understand expectations and are able to contribute optimally. When these elements are implemented effectively, performance management becomes not only a monitoring tool but also a strategic mechanism to foster long-term organizational sustainability.